Use of Tolvaptan in a Patient With Palliated Congenital Heart Disease. Issue 1 (January 2018) - Chakravarti, Sujata; Busovsky-McNeal, Melissa
Heart failure is a common problem in the ever growing population of patients with palliated congenital heart disease. It is frequently complicated by hyponatremia that has been associated with increased morbidity and mortality. Tolvaptan is a vasopressin receptor antagonist that has been effective in improving hyponatremia and congestive symptoms in adults with chronic heart failure. We describe the short-term use of tolvaptan to treat hyponatremic hypervolemia in an adolescent patient with chronic heart failure in the setting of palliated congenital heart disease prior to definitive surgical intervention. In this case, the patient had improvement in hyponatremia and a decrease in body weight, without any adverse effects.